Kesesuaian Sistem Akuntansi PELINDO dengan Kriteria Business Ready (B-READY) Bank Dunia - Adnyana, I Wayan Diana Putra; Sudama, I Made (UMSurabaya Publishing, 2025)
This study investigates the alignment of PT Pelabuhan Indonesia (Pelindo)’s accounting system with the World Bank’s Business Ready (B-READY) criteria, aiming to evaluate conformity, identify improvement areas, and propose strategic enhancements. Employing a qualitative case study approach, data were collected through document analysis of Pelindo’s financial reports, annual reports, and World Bank publications, supplemented by insights from recent literature on digital transformation in ports. Results indicate 72% compliance with B-READY indicators, with high alignment in financial reporting transparency (85%) and low in technology integration (65%). Key gaps include the lack of an integrated real-time reporting platform and insufficient staff training on B-READY standards. Discussions highlight Pelindo’s adoption of IFRS for transparency, yet fragmented digital efforts compared to global ports using cloud-based systems. Recommendations include implementing a cloud-based accounting system and collaborative training with the World Bank. This research underscores technology adoption as critical for B-READY compliance, contributing theoretically to digital accounting literature in global business readiness and practically providing a roadmap for Pelindo to enhance competitiveness and Indonesia’s logistics system.